Papers of Samuel Shumack - Shumack, Samuel, 1850-1940.; Shumack, John Everest (1856)
1. MS diary kept by Samuel Shumack describing the pioneering days of the Canberra district. 2. Bundle of newspaper cuttings, (Queanbeyan Age 1920-1940) including articles on early Canberra by an 'Old Identity' and 'that Other Old Identity' & notices of Shumack's death. 3. Memoirs completed June 1938. Additional diary by J.E. Shumack, 1938-1952 with notes of family history and press cuttings. 4. Typed copy of S. Shumack's autobiography, typed by Samuel Shumack, Jr. The first 56 pages condensed version of the original, while the rest is an exact transaction. [Explanatory letter attached]
Manuscript reference no. : MS 1861.
Keywords: Shumack, John Everest -- Archives; Pioneers -- Australian Capital Territory -- Archives; Canberra (A.C.T.) -- History; Pioneers